2006
DOI: 10.1590/s0101-81752006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Análise quali-quantitativa da ictiofauna acompanhante na pesca do camarão sete-barbas, na Armação do Itapocoroy, Penha, Santa Catarina

Abstract: A ictiofauna acompanhante na pesca de camarão sete-barbas foi estudada mensalmente entre agosto 1996 a julho 2003 nas áreas de atuação da pesca artesanal na Armação do Itapocoroy, Penha. Foram utilizadas duas redes-de-arrasto com portas, malha de 3,0 cm na manga e corpo e de 2,0 cm no ensacador, tracionada por baleeira com velocidade média de 2,0 nós. A temperatura e salinidade média da água de fundo mantiveram um padrão uniforme de flutuação sazonal, sem diferença significativa entre os anos de coleta. Das 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2
20

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 13 publications
3
35
2
20
Order By: Relevance
“…The relationship between the number of species and families (2.45) was slightly smaller than values recorded in similar studies of demersal fish assemblages in State of Paraíba (2.76) (Nunes & Rosa 1998) and Balneário de Atami, State of Paraná (2.69) (Godefroid et al 2004), while being somewhat larger than that registered in a comparable study carried out in Penha, State of Santa Catarina (2.14) (Branco & Verani 2006). Thus, it remains unclear whether there are latitudinal trends in species/families ratios and their potential ecological or biogeographic significance.…”
Section: Discussioncontrasting
confidence: 64%
“…The relationship between the number of species and families (2.45) was slightly smaller than values recorded in similar studies of demersal fish assemblages in State of Paraíba (2.76) (Nunes & Rosa 1998) and Balneário de Atami, State of Paraná (2.69) (Godefroid et al 2004), while being somewhat larger than that registered in a comparable study carried out in Penha, State of Santa Catarina (2.14) (Branco & Verani 2006). Thus, it remains unclear whether there are latitudinal trends in species/families ratios and their potential ecological or biogeographic significance.…”
Section: Discussioncontrasting
confidence: 64%
“…Although species richness in our samples was high, nine and seven species were numerically dominant in Balneário Barra do Sul and Penha, respectively, which is a common characteristic observed in demersal fish associations (ANSARI et al 1995, CHAVES et al 2003, BRANCO & VERANI 2006a.…”
Section: Resultsmentioning
confidence: 55%
“…Sampling took place at the traditional seabob shrimp fishing areas, for one hour, at depths ranging from 5 to 25 m. In each region, three fishing hauls (samples) were performed in the traditional seabob shrimp fishing areas for one hour each during the morning period, at depths from 5 to 25 m. Although it is mentioned in the literature that depth can influence species composition (CHAVES et al 2003, SOUZA et al 2008, no differences were observed in the assemblies caught between 5 and 25 meters in previous studies conducted in the Penha region (BAIL & BRANCO 2003, BRANCO & VERANI 2006a; therefore, we adopted trawls among these isobaths to compose representative samples of the regions. A double-rig shrimp vessel equipped with two bottom trawls with 3 cm mesh in the sleeve and 2 cm mesh in the trawl bag, was used for trawling, conducted at an average speed of two knots (BRANCO 2005).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…A legislação vigente (Portaria Sudepe 04, 14/01/86) permite somente artes de pesca passivas como o aviãozinho, embora sejam também utilizadas ilegalmente redes de arrasto manual (coca e berimbau ou gerival) e motorizados (prancha ou portas). A proibição das artes de pesca ativa baseia-se na alta proporção em peso de peixes não aproveitados, o que poderia contribuir para um alto impacto desta atividade do ponto de vista econômico e biológico (SAILA 1983, HUDSON & FURNESS 1988, WASSENBERG & HILL 1989, MURRAY et al 1992, ALVERSON et al 1994, VIEIRA et al 1996, CLUCAS 1997, BRANCO & VERANI 2006. De fato, os resultados do bycatch da rede aviãozinho apresentados para a Lagoa dos Patos, quando comparados com as redes de arrasto, caracterizam o aviãozinho como uma arte de pesca eficiente e razoavelmente adequada à pesca estuarina e, neste sentido, fundamenta a Portaria Sudepe 04, 14/01/86.…”
Section: Revista Brasileira De Zoologia 23 (4): 1016-1028 Dezembro 2006unclassified